Hubungan Antara Lingkungan Teman Sebaya Dengan Kemampuan Interaksi Sosial Anak Di TPA/TPQ Baitussalam Sawah Liat Kabupaten Pesisir Selatan - Sardelina, Annisa; Natsir, MHD (Universitas Negeri Padang, 2025)
This research is motivated by the lack of children's ability to interact socially, and the lack of children's willingness to cooperate with other children or their peers. The purpose of the research activity is to find out the description of: children's peer environment, children's social interaction abilities, the relationship between peer environment and children's social interaction abilities at TPA/TPQ Baitussalam Sawah Liat, Pesisir Selatan Regency. The research was conducted using a quantitative approach with a correlational type. The research population was children who studied at TPA/TPQ Baitussalam Sawah Liat, Pesisir Selatan Regency. Meanwhile, the research sample was taken using the total sampling technique. The research instrument in data collection used a questionnaire. The data analysis technique used the percentage formula and rank order. The results of the study showed that: (1) Children's peer environment is categorized as less good; (2) Children's social interaction abilities are categorized as low, and; (3) There is a significant relationship between peer environment and children's social interaction abilities at TPA/TPQ Baitussalam Sawah Liat, Pesisir Selatan Regency.